The role of history in knowing ourselves = Rola historii w poznaniu siebie - Sinani, Gjergj (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author discusses the role of the narrative about the past as a valuable lesson of morality. Drawing lessons from the past is the way of linking it with the present and the future. Judgments and opinions about history are based on a moral and political critique of the past. Therefore, clarifying the links between justice, morality and history is very important. The experience of totalitarianism presented as the unlimited power of government in all areas of individuals? life restricted human rights, democracy and rule of law, and it also made private initiative and the ownership rights disappear.
Keywords: historia; ustna historia; totalitaryzm; moralność; filozofia; history; gral history; totalitarism; morality; philosophy